Photoinduced reaction mechanisms in prototypical and bathy phytochromes. Issue 19 (9th May 2022) - López, María Fernández; Dahl, Margarethe; Escobar, Francisco Velázquez; Bonomi, Hernán Ruy; Kraskov, Anastasia; Michael, Norbert; Mroginski, Maria Andrea; Scheerer, Patrick; Hildebrandt, Peter
Abstract : Resonance Raman and IR spectroscopies reveal a common mechanistic pattern of prototypical and bathy phytochrome including chromophore isomerization, proton transfer, and protein structural changes. Abstract : Phytochromes, found in plants, fungi, and bacteria, exploit light as a source of information to control physiological processes via photoswitching between two states of different physiological activity, i.e. a red-absorbing Pr and a far-red-absorbing Pfr state. Depending on the relative stability in the dark, bacterial phytochromes are divided into prototypical and bathy phytochromes, where the stable state is Pr and Pfr, respectively. In this work we studied representatives of these groups (prototypical Agp1 and bathy Agp2 from Agrobacterium fabrum ) together with the bathy-like phytochrome Xcc BphP from Xanthomonas campestris by resonance Raman and IR difference spectroscopy. In all three phytochromes, the photoinduced conversions display the same mechanistic pattern as reflected by the chromophore structures in the various intermediate states. We also observed in each case the secondary structure transition of the tongue, which is presumably crucial for the function of phytochrome. The three phytochromes differ in details of the chromophore conformation in the various intermediates and the energetic barrier of their respective decay reactions. The specific protein environment in the chromophore pocket, which is most likely the origin for these small differences, also controls the proton transfer processes concomitant to the photoconversions. These proton translocations, which are tightly coupled to the structural transition of the tongue, presumably proceed via the same mechanism along the Pr → Pfr conversion whereas the reverse Pfr → Pr photoconversion includes different proton transfer pathways. Finally, classification of phytochromes in prototypical and bathy (or bathy-like) phytochromes is discussed in terms of molecular structure and mechanistic properties.